Slay bells and satchels - Howell, Dorothy (Dorothy A.) (Howell, Dorothy (Dorothy A.). Haley Randolph mystery., 2012)
"The Summer Santa Sale at Holt's Department becomes a Christmas nightmare when sales clerk Haley Randolph finds a murdered elf in the store's giant toy bag. Haley, a crazed fashionista obsessed with designer handbags, could find herself 'bagged' if she doesn't untangle this mystery quicker than Saint Nick can slide down a chimney. But Haley has another problem: Can working with hot private detective Jack Bishop put her on Santa's 'naughty' list?"--P.[4] of cover.